2019
DOI: 10.1038/s41598-019-50965-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite exposure suppresses adipogenesis, mitochondrial biogenesis and thermogenesis via autophagy inhibition in brown adipose tissue

Abstract: Arsenite, a trivalent form of arsenic, is an element that occurs naturally in the environment. Humans are exposed to high dose of arsenite through consuming arsenite-contaminated drinking water and food, and the arsenite can accumulate in the human tissues. Arsenite induces oxidative stress, which is linked to metabolic disorders such as obesity and diabetes. Brown adipocytes dissipating energy as heat have emerging roles for obesity treatment and prevention. Therefore, understanding the pathophysiological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…Another recent study corroborated Zuo et al 2019's findings in male C57BL/6J mice exposed to 5 and 10 ppm arsenic for 9 d (Bae et al 2019). Bae et al (2019) reported arsenic accumulation in BAT, with a significant decrease in lipogenesis, autophagy, and thermogenesis (Bae et al 2019). The authors also found arsenite exposure to impair differentiation of HIB1B brown preadipocytes following a 6-d exposure to arsenite at 2.5-, 5-, and 10-lM concentrations (Bae et al 2019).…”
Section: Insulin-stimulated Glucose Uptake and Glucose Transportsupporting
confidence: 62%
See 2 more Smart Citations
“…Another recent study corroborated Zuo et al 2019's findings in male C57BL/6J mice exposed to 5 and 10 ppm arsenic for 9 d (Bae et al 2019). Bae et al (2019) reported arsenic accumulation in BAT, with a significant decrease in lipogenesis, autophagy, and thermogenesis (Bae et al 2019). The authors also found arsenite exposure to impair differentiation of HIB1B brown preadipocytes following a 6-d exposure to arsenite at 2.5-, 5-, and 10-lM concentrations (Bae et al 2019).…”
Section: Insulin-stimulated Glucose Uptake and Glucose Transportsupporting
confidence: 62%
“…Moreover, insulin levels were significantly elevated at both concentrations of exposure, with a significant decrease in genes involved in thermogenesis [uncoupling protein 1 (UCP1) and PGC1a] and mitochondrial respiratory chain activity [Cytochrome C Oxidase Subunit IV (COXIV) and NADH:Ubiquinone Oxidoreductase Subunit S4 (NDUFS4)] (Zuo et al 2019). Another recent study corroborated Zuo et al 2019's findings in male C57BL/6J mice exposed to 5 and 10 ppm arsenic for 9 d (Bae et al 2019). Bae et al (2019) reported arsenic accumulation in BAT, with a significant decrease in lipogenesis, autophagy, and thermogenesis (Bae et al 2019).…”
Section: Insulin-stimulated Glucose Uptake and Glucose Transportmentioning
confidence: 57%
See 1 more Smart Citation
“…Specifically, oral administration of NaAsO 2 (5–10 mg/kg) to male C57BL/6J mice was accompanied by a more pronounced As accumulation in BAT as compared with WAT and also resulted in inhibition of brown adipocyte differentiation and decreased expression of PPARγ and other brown adipocyte-specific markers (UCP1 and PGC1). Moreover, As-induced inhibition of autophagy was proposed to play a role in BAT dysfunction 50 . Correspondingly, prolonged exposure of adult C57BL/6J female mice to inorganic As (5–20 ppm in drinking water for 17 weeks) was shown to impair energy homeostasis, resulting in metabolic disturbances attributed to BAT whitening and impaired thermogenesis 51 .…”
Section: Adipotropic Effects Of Heavy Metalsmentioning
confidence: 99%
“…Arsenic exposure inhibited the differentiation of BAT and lowered expression of PPARγ, UCP1 and PGC1α, which are defining features of brown adipocytes ( 115 ). Arsenite, similarly reduced BAT differentiation, decreased mitochondrial functioning, and lowered thermogenesis in BAT by reducing UCP1 expression ( 117 ). Arsenite accumulates in BAT and suppressed Sestrin2 phosphorylation by ULK1, which under normal conditions, promotes the antioxidant effects of Sestrin2 against ROS that form within the cells ( 117 , 118 ).…”
Section: Metalsmentioning
confidence: 99%